Playing senior inter-county Gaelic games: Experiences, realities and consequences - Elish Kelly; Joanne Banks; Séamus McGuinness; Dorothy Watson (The Economic and Social Research Institute (ESRI), 2018)
This study, commissioned by the GAA and the GPA, uses data from a survey of 2016 players to examine the commitments required to play senior inter-county Gaelic games, and the impact that this has on players' personal and professional lives, and their club involvement.
Keywords: 330